„Królewska duma z wielkiej niepomyślności”1. Doświadczenie emigracji w poetyckiej perspektywie Lwa Gomolickiego - Brzykcy, Jolanta (Acta Polono-Ruthenica, 2018)
The paper discusses the functioning of emigration theme in the poetry of Leo Gomolitzky (1903-1988) - one of the greatest representative of Russian diaspora in Poland before World War II. Some poetical texts and two poems (Warsaw, The emigre poem) has been analized in it, in the context of bilingualism, exterritoriality and biculturalism - categories, that had a strong influence on Gomolitzky’s life and works. In the analized texts Gomolitzky shows his own experiences and thoughts caused by the emigration, he also diagnoses people’s attitudes toward exile. From the viewpoint of the poet the emigration is, undoubtedly, the catastrophe, but at the same time Gomolitzky interpretates it as a chance of the moral renewal, spiritual rebirth.